2014
DOI: 10.1016/j.matbio.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and proteomic analysis of osteoarthritis

Abstract: Our friend and colleague, Dr. Dick Heinegård, contributed greatly to the understanding of joint tissue biochemistry, the discovery and validation of arthritis-related biomarkers and the establishment of methodology for proteomic studies in osteoarthritis (OA). To date, discovery of OA-related biomarkers has focused on cartilage, synovial fluid and serum. Methods, such as affinity depletion and hyaluronidase treatment have facilitated proteomics discovery research from these sources. Osteoarthritis usually invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 81 publications
0
47
0
3
Order By: Relevance
“…Proteomics methods have identified many proteins that may relate to pathological mechanisms of OA (for review see [25]). For instance, the OA synovial fluid proteome implicates proteins related to formation and remodeling of the extracellular matrix [26], and the acute-phase response signaling pathway, the complement pathway, and the coagulation pathway [27].…”
Section: The Diseasementioning
confidence: 99%
“…Proteomics methods have identified many proteins that may relate to pathological mechanisms of OA (for review see [25]). For instance, the OA synovial fluid proteome implicates proteins related to formation and remodeling of the extracellular matrix [26], and the acute-phase response signaling pathway, the complement pathway, and the coagulation pathway [27].…”
Section: The Diseasementioning
confidence: 99%
“…An example of proteoglycan versatility comes in the form of perlecan, an immense heparan sulfate proteoglycan primarily localized to basement membranes and pericellular spaces [4–9]. The modular structure of perlecan enables homeostatic regulation within a vast array of cellular processes including cell adhesion [10,11], endocytosis [12], bone and cartilage formation [1316], lipid metabolism [17], peripheral node assembly [18], inflammation and wound healing [19,20], thrombosis [21], cancer angiogenesis [9,11,22–33], cardiovascular development [34], and autophagy [35,36]. Given the gargantuan structure and multitude of functions of perlecan, it is no surprise that its gene, HSPG2 , is similarly large and transcriptionally controlled by complex promoter interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a peptidomics study identified three urinary fibrinogen peptides as biomarkers for necrotizing enterocolitis, a leading cause of morbidity and mortality in premature infants 13. Similarly, shotgun proteomics has been used in biomarker studies for renal and urinary tract diseases14 and disease conditions, not in anatomical proximity to the site of sample collection, such as cancer,15 aging,16 osteoarthritis,17 and preeclampsia 18. Urine has also been pre-fractionated to characterize subsets of its proteome, which include exosomes and microparticles.…”
Section: Introductionmentioning
confidence: 99%